Antibacterial Effectiveness of Golden Garlic Against Gram-Positive Bacteria from Diabetic Ulcer Patients with High CRP Levels - Erawati, Erawati; Imasari, Triffit; Wardani, Siska Kusuma (Newinera Publisher, 2025)
The wrong antibiotic therapy in patients with DM results in therapeutic failure and increases the risk of antibiotic resistance. Herbal ingredients can be used as antibacterial alternatives to prevent the growth of Gram-positive bacteria so that there is no resistance and further complications from diabetics. One of the natural antibacterial alternative herbs is Golden garlic or golden coloured garlic extract. Golden garlic contains the bioactive component Allisin as an antibacterial on several pathogenic bacteria, such as Gram-positive bacteria. Based on this, the purpose of the study was to analyze the Antibacterial Effectiveness of Golden Garlic Against Gram-Positive Bacteria From Patients With Diabetic Ulcers With High CRP Levels. Research design with analytical observational method and cross sectional research design, purposive sampling technique. Samples with high CRP from diabetic ulcer swabs were 10 samples with the results of Staphylococcus aureus bacterial growth and tested the effectiveness of golden garlic ethanol extract with concentrations of 100%, 80%, 60% and 40%. The results of the study of golden garlic extract with Cindamycin positive control showed intermediate effectiveness in inhibiting the growth of Gram-positive bacteria with a concentration of 100%, while with concentrations of 80%, 60% and 40% showed more resistance. Analysis with SPSS Anova there is a difference in effectiveness by showing the inhibition zone of Golden Garlic with a concentration of 100%, 80%, 60% and 40% against Gram Positive Bacteria from Diabeticum Ulcer Patients with High CRP Levels of 0.000. The results showed that Golden Garlic extract can be an alternative to antibacterial herbs in diabetic ulcers.